Plataformização, multimodalidade e semiótica: uma análise da disciplina de Língua Portuguesa pelo portal NetEscola - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
Contemporary times have enabled society to live on/life, giving rise to the prevailing ethos of ubiquity. The development of digital technologies has intensified human-machine interaction. This study takes place in a paradigm tensioned by national curriculum proposals (Brasil, 2018), institutional demands for access to multi-platforms (Brasil, 2023, Goiás, 2018), and the local reality experienced by basic public education in Goiás. Based on the researcher's experiences, the aim is to problematize: what are the implications of the teaching approach used by the Portal NetEscola platform? To this end, the aim is to understand the perspectives for teaching Portuguese to the 9th grade on the Portal NetEscola platform. To this end, a literature review is carried out in the context of platformization, multimodality, and semiotics. The methodological approach is qualitative; the objectives are exploratory, and the procedures are bibliographical and close to netnography. The criteria for analysis correspond to the architecture and structure of the platform and the pedagogical materials proposed for teaching and learning Portuguese for the 9th grade. The theoretical basis uses the concepts of digital technologies (Feenberg, 2010; Cesarino, 2021; Santaella and Kaufman, 2021), digital culture (Castells, 2005; Santaella, 2021, 2022), platformization (Poell; Neiborg; Van Dijck, 2020; D'Andrea, 2020) and current curricula (Brazil, 2023; 2018; Goiás, 2018). In order to understand the teaching of reading and writing in language classes, the studies of multiliteracy (Cazden et al., 2021), multimodality (Kress; Van Leeuwen, 2001), literacy (Kalantzis; Cope; Pinheiro, 2020) and critical multimodal literacy (Buzato, 2007a; 2007b; 2019) are used. We identified a scenario submerged in power relations, platformization, and granted by surveillance and data control. Although the platform is characterized as a multimodal portal and derived from multi-platforms, there is no evidence of multimodal articulation in its approach, which enhances multisemiotic empowerment for 9th-grade Portuguese language classes on this network
Platformization, multimodality and semiotics: an analysis of the Portuguese Language subject on the Portal NetEscola
Keywords: Educação - Plataformização - Portal Net Escola; Plataformização - Multimodalidade - Semiótica - Portal Net Escola; Portal NetEscola - Plataformização - Língua Portuguesa; Platformization - Portal Net Escola; Platformization - Multimodality - Semiotics - Portal Net Escola; Portal Net Escola - Portuguese Language; CIENCIAS HUMANAS::EDUCACAO